Dacochile microsoma Poinar & Brown, not a tanyderid but a bruchomyiine psychodid (Diptera: Psychodidae, Tanyderidae) - Woodley, Norman E. (Zootaxa, 2005)
A review of the characters used by Poinar & Brown (2004) to place their new fossil fly from Burmese amber, Dacochile microsoma, in the family Tanyderidae conclusively demonstrates that the fly actually belongs to the subfamily Bruchomyiinae in the family Psychodidae.